2022
DOI: 10.1063/5.0088527
|View full text |Cite
|
Sign up to set email alerts
|

Impact of gaps on the flow statistics in an emergent rigid canopy

Abstract: High-resolution large eddy simulations and complementary laboratory experiments using particle image velocimetry were performed to provide a detailed quantitative assessment of flow response to gaps in cylinder arrays. The base canopy consists of a dense array of emergent rigid cylinders placed in a regular staggered pattern. The gaps varied in length from [Formula: see text] to 24, in intervals of 4 d, where d is the diameter of the cylinders. The analysis was performed under subcritical conditions with Froud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…According to Ranjan et al. (2022), the measuring gap regions affected by the upstream vegetation stems have a short extent. Turbulence strength downstream of the array reaches the maximum value within one unit of the diameter length, 1 d, and then transitions from an exponential to a power‐law decay, quickly dropping back to a minimum value within four units of the diameter length, 4 d, suggesting that the closest two rows of the canopy upstream from the measuring gap would have the highest influence to the flow pattern.…”
Section: Resultsmentioning
confidence: 99%
“…According to Ranjan et al. (2022), the measuring gap regions affected by the upstream vegetation stems have a short extent. Turbulence strength downstream of the array reaches the maximum value within one unit of the diameter length, 1 d, and then transitions from an exponential to a power‐law decay, quickly dropping back to a minimum value within four units of the diameter length, 4 d, suggesting that the closest two rows of the canopy upstream from the measuring gap would have the highest influence to the flow pattern.…”
Section: Resultsmentioning
confidence: 99%
“…The numerical domain for both the vegetated and non-vegetated channel flows is similar to that simulated in Ranjan et al (2022). The channel is 15 cm wide and 10 cm high, with staggered array of rigid emergent cylinders of diameter d = 6.25 mm and solid volume fraction ϕ = 0.088, as shown in Figure 3b.…”
Section: Comparison With Data From Numerical Simulations (Les)mentioning
confidence: 89%
“…The simulations were conducted for 12.11 flow-through times (the number of times a fluid parcel is advected through the entire domain during the simulation duration) while the time averaging was done over the last 5.05 flow-through times when the flow had reached a steady state. Ranjan et al (2022) simulated hydrodynamics of a similar canopy and reported the effect of canopy gaps on the mean and higher order statistics. More details of the numerical solver, mesh, and validation of the numerical model is presented in Ranjan et al (2022).…”
Section: Comparison With Data From Numerical Simulations (Les)mentioning
confidence: 99%
See 2 more Smart Citations